Transforming lives: Combating digital health inequality. (October 2019) - Gann, Bob
For those who are connected digitally, the digital health revolution is an enormous opportunity for patient empowerment. However, half the world's population are not online. Those who are least likely to be online are exactly those who experience the greatest burden of ill health. As information about health and illness is increasingly (and often exclusively) available in digital form, we face a new public health challenge – digital health inequality. Libraries are ideally placed to reach these population groups who may be hardest to reach. The IFLA (2017) Statement on Digital Literacy recognises that with libraries' mission to help all their users access and apply the information they need for personal and community development, digital inclusion is an important part of the practice of librarianship. Successful interventions to improve digital inclusion involve targeting connecting, and transforming lives. This article focuses on initiatives to combat digital exclusion in England and Wales.